11 - Social Capital and Food Security amongst Women in Smallholder Farming in the Face of Climate Change in Bikita, Zimbabwe - Owen, Mafongoya (Africa Development, 2022)
Food insecurity is a devastating setback for vulnerable women in smallholder farming in Zimbabwe. Women’s low or limited adaptive capacity is caused by diverse factors, including , which include poverty, an unstable economy, political crisis and climate change. Adaptive strategies that differ from the conventional national and civic interventions to circumvent these factors have yielded subtle food security outcomes. As a result, there are growing calls for the adoption of social capital as an alternative grassroots-based adaptive strategy. This study examined the potential for and challenges faced by women who use social capital in adapting to food insecurity. Using in-depth interviews, focus group discussions and key informant interviews it revealed that women in smallholder farming were utilising bonding, bridging and linking capital as a means of adaptation. These three types of capital were operationalised in four projects: Food For Assets (FFA), community gardening, the Boer goat project and Fushai. It emerged that three of the projects performed better in some wards but did not do well in others. Despite its potential, the Boer goat project was riddled with challenges, which emanated from the absence of bonding capital. I therefore conclude and recommend that social capital is critical for women in food insecurity adaptation. However, it needs to be buttressed by a harmonious relationship between the three forms of social capital and all stakeholders for sustainability to be realised.